Goldenhar Syndrome: A Rare Case Report - Badal, Md. Fakhrul Amin; Islam, Saiful; Masuduzzaman, Shah Mohammad; Talukder, Md. Noor Uddin; Alam, Md. Jamshed; Islam, Md. Shafiqul; Khan, Md. Kamrul Ahsan (The Insight, 2021)
Goldenhar syndrome or oculo-auriculo-vertebral syndrome is a sporadic or autosomal dominant, inherited genetic rare syndrome that includes limbal dermoid or lipodermoid, pre-auricular tags, hemifacial asymmetry and vertebral anomalies. The phenotype is highly variable. Goldenhar syndrome is one of the variants of craniofacial anomalies. The etiology of this rare disease is not fully understood, as it has shown itself variable genetically and of unclear causes. It is usually unilateral and the age of onset is usually during neonatal & infancy. The purpose of this article is to report this rare syndrome of craniofacial malformations, which may aware physicians to make its diagnosis